Debt and Taxes and Uncertainty - ROSS, STEPHEN A. (Journal of Finance, 1985)
ABSTRACT With a graduated personal tax schedule, Miller showed that there could be an equilibrium debt supply for the corporate sector as a whole. In the presence of uncertainty there is also a unique debt/equity ratio for each individual firm, and this ratio is related to the firm's operational risk characteristics. However, if firms merge and spin off in response to tax incentives, the identity of firms is ambiguous and only the corporate sector is a meaningful construct. These arguments are developed in both discrete and continuous models that employ extensions of the arbitrage‐free pricing theory.